1α, 25-dihydroxyvitamin D3-eluting nanofibrous dressings induce endogenous antimicrobial peptide expression. (4th July 2018) - Jiang, Jiang; Zhang, Yang; Indra, Arup K; Ganguli-Indra, Gitali; Le, Mai N; Wang, Hongjun; Hollins, Ronald R; Reilly, Debra A; Carlson, Mark A; Gallo, Richard L; Gombart, Adrian F; Xie, Jingwei
Aim: The aim of this study was to develop a nanofiber-based dressing capable of local sustained delivery of 1α, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ) and augmenting human CAMP induction.Materials & methods: Nanofibrous wound dressings containing 1, 25(OH)2 D3 were successfully prepared by electrospinning, which were examined in vitro, in vivo and ex vivo .Results: 1, 25(OH)2 D3 was successfully loaded into nanofibers with encapsulation efficiency larger than 90%. 1, 25(OH)2 D3 showed a sustained release from nanofibers over 4 weeks. Treatment of U937 and HaCaT cells with 1, 25(OH)2 D3 -loaded poly(ϵ-caprolactone) nanofibers significantly induced hCAP18/LL37 expression in monocytes and keratinocytes, skin wounds of humanized transgenic mice and artificial wounds of human skin explants.Conclusion: 1, 25(OH)2 D3 containing nanofibrous dressings could enhance innate immunity by inducing antimicrobial peptide production.